Energy Expenditure and Shivering Severity During Targeted Temperature Management at 36°C After Cardiac Arrest: A Case Series. Issue 3 (July 2020) - Cordoza, Makayla; Chan, Lingtak-Neander; Bridges, Elizabeth; Carlbom, David J.; Thompson, Hilaire
Abstract : Patients undergoing targeted temperature management (TTM) after cardiac arrest are at risk for shivering, which increases energy expenditure (EE) and may attenuate TTM benefits. This article reports patterns of EE for patients with and without shivering who received TTM at 36°C after cardiac arrest. Based on 96 case assessments, there were 14 occasions when more than one 15-minute interval period was required to appropriately modify the Bedside Shivering Assessment Scale (BSAS) score. Investigators noted that although higher EE was related to higher BSAS scores, there may be opportunities for earlier detection of shivering.